Auditoria operativa y su incidencia en el área administrativa del Gobierno Autónomo Descentralizado parroquial rural de San Sebastian del cantón Pichincha, año 2014 - Jacho Zambrano, María Victoria (2016)
The present study was developed within the Autonomous Government Decentralized rural parish of San Sebastián located in the canton of Pichincha province of Manabí. The objectives that have been raised for conducting the performance audit includes analysis of administrative processes that will reveal the activities to be carried out in each process is defined, also the degree of efficiency and compliance with the law to be applied will be evaluated within the institution, management and financial indicators were also defined to meet a more realistic perspective of the organization, culminating in an audit report. The methods used were inductive, deductive, analytical and systematic which allowed to investigate, draw conclusions and make an analysis of the current situation of the organization. For the development of this study documentary and field research it was used and techniques such as surveys, interviews and internal control questionnaires to obtain information were applied. Indeed this paper determined the various irregularities revealed in the administrative processes for the proper operational functioning, they do not allow this organism to develop efficiently with the implementation of financial and management indicators was identified that activities revolve around the institution they are not efficient or effective, operational audit report to senior management in which it is disclosed relevant facts with appropriate conclusions and recommendations to improve decision-making in the organization was issued.